2019
DOI: 10.1101/711564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of size and elasticity on the relation between flow velocity and wall shear stress in side-wall aneurysms: A lattice Boltzmann-based computer simulation study

Abstract: Blood flow in an artery is a fluid-structure interaction problem. It is widely accepted that aneurysm formation, enlargement and failure are associated with wall shear stress (WSS) which is exerted by flowing blood on the aneurysmal wall. To date, most of the computational studies of this problem assume rigid walls. In particular, in the case of side-wall aneurysms, the combined effect of aneurysm size and wall elasticity on intra-aneurysm (IA) flow characteristics is poorly understood. Here we propose a model… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…To examine the role of geometry [14,37,49,50] for the above-described observation, we have conducted simulations of pulsatile flow through a curved tube without aneurysm (Fig. 8) and a different ideal aneurysm (Fig.…”
Section: Effects Of Tissue Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the role of geometry [14,37,49,50] for the above-described observation, we have conducted simulations of pulsatile flow through a curved tube without aneurysm (Fig. 8) and a different ideal aneurysm (Fig.…”
Section: Effects Of Tissue Degradationmentioning
confidence: 99%
“…Numerical simulations provide a promising alternative. In a recent study [14] we have shown that blood flow inside an aneurysm exhibits complex features (such as flow disturbances) associ-ated with wall softness. Also fluid-structure interaction (FSI) simulations with complex wall models [15] have unveiled significant effects on WSS even in simplified arteries.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the role of geometry (Lee et al 2008;Kurşun et al 2018;Wang et al 2020Wang et al , 2021 for the above-described observation, we have conducted simulations of pulsatile flow through a curved tube without aneurysm (Fig. 8) and a different ideal aneurysm (Fig.…”
Section: Effects Of Tissue Degradationmentioning
confidence: 99%
“…Numerical simulations provide a promising alternative. In a recent study (Wang et al 2020), we have shown that blood flow inside an aneurysm exhibits complex features (such as flow disturbances) associated with wall softness. Also fluidstructure interaction (FSI) simulations with complex wall models (Balzani et al 2016) have unveiled significant effects on WSS even in simplified arteries.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we show that the ANN should not be omniscient, but it should carefully replicate the input-output structure of the ENS. Moreover, in multiphysics simulations, diseased states are usually hardcoded into the model [5,[12][13][14][15]. This study introduces a multiphysics + ANN model of the healthy intestine that, under certain conditions, 'becomes diseased' without the need to hardcode the disease state into the model.…”
Section: Introductionmentioning
confidence: 99%